Indicators From China’s Listed Corporations on Corporate Financing Behavior and Policy-Related Risk - Zhang, Wenlong; Ausaf, Muhammad Arslan; Jahangir, Junaid (Frontiers in Psychology, 2022)
This study explores corporate financing behavior regarding the company and country-level factors and risks associated with policy-related regulations. The study considers all three categories of risk: geopolitical risk, economic policy uncertainty, and political risk. In addition to this, we investigated how the links between diverse types of financing activities and the policy-related risks associated with them change depending on the type of financing strategy utilized (debt vs. equity). The study examined quarterly data from 2016Q1 to 2020Q3. Findings show financial restrictions, as well as inequities within the sector, have an impact on corporate investment while policy-related risks might impact a company's financing selections. Compared to equity financing, debt financing is more susceptible to policy-related risk. According to the available information, features at the company and nation levels also impact corporate finance choices. Finally, firms that have little financial resources are more susceptible to the adverse effects of policy-related risk than industrial companies are. Managers, as well as governments, should utilize these insights to design economic strategies that are more successful in the future.